Fabrication of Aligned Side-by-Side TiO2/SnO2 Nanofibers via Dual-Opposite-Spinneret Electrospinning. (21st February 2012) - Xu, Fu; Li, Luming; Cui, Xiaojie
Abstract : Well-aligned and uniform side-by-side bicomponent fibers have been produced via dual-opposite-spinneret electrospinning. Side-by-side TiO2 /SnO2 nanofibers were obtained after calcining as-spun fibers. The thermal degradation of the electrospun fibers was evaluated using combined thermogravimetry and differential thermal analysis (TG-DTA), and the crystal structure of calcined nanofibers was investigated by X-ray diffraction (XRD). The fabricated TiO2 /SnO2 nanofibers expose both TiO2 mainly consisting of anatase phase and rutile-type SnO2 to the surface, which is appropriate for photocatalytic materials.